Protéger des espaces naturels - Fabien Milanovic (Revue d'anthropologie des connaissances)
With the consideration that the relationships between humans and nature are constitutive of the dynamics of the ecosystems, contemporary ecological conceptions point toward new stakes in nature conservation. The issue at stake is not any more to protect the nature in sanctuaries but to manage the local biodiversity by integrating human activities within its definition. This text explores these evolutions at the level of the modalities of management of natural reserves, through a case study (Regional Natural Park of Camargue, France). We highlight two pragmatic regimes of management, both of which illustrate the diversity of the relationships which are possible to establish with nature, depending upon the combinations realised between anthropic and natural disturbances and the normative or ethics supports underlying the relationships to the living entities. The conclusion addresses the renewal of the contemporary practices and issues in the management of nature.